16 years follow-up evaluation of immediate vs delayed vs. combined hormonal therapy on fertility of patients with cryptorchidism: results of a longitudinal cohort study - Riccardo Bartoletti; Antonio Luigi Pastore; Filippo Menchini Fabris; Tommaso Di Vico; Riccardo Morganti; Andrea Mogorovich; Girolamo Morelli; Diego Peroni; Yazan Al Salhi; Alessandro Zucchi (BMC, 2022)
Abstract Background To investigate in a longitudinal cohort study, the best treatment to preserve fertility in cryptorchid subjects. Patients treated with immediate hormonal vs. delayed vs. combined (hormone plus surgery) therapy consecutively enrolled during the period 1987-1997, were evaluated. Methods Two hundred fifty-five subjects were enrolled and 192 patients completed the follow-upt. One hundred fifty-six patients and 36 out 192 had monolateral and bilateral cryptorchidism, respectively. Twenty-nine out of 192 were previously treated by surgery alone (Group A), 93/192 by hormone therapy alone (Group B), 51/192 received sequential combined hormone therapy plus surgery (Group C) whilst 19/192 refused any type of treatment (Group D). The other 63 patients were considered lost to follow-up. All the patients underwent medical consultation, scrotal ultrasound scan, sperm analysis and Inhibin B, Follicular Stimulating Hormone (FSH) and Testosterone (T) serum level determination. Results Testicular volume was found decreased in the Group D patients whilst hormone serum levels were comparable in all groups. Statistically significant differences for sperm characteristics were found in patients treated with hormonal therapy alone or combined with surgery (Groups B and C). These two groups reported better semen quality than patients who received surgery alone or no treatment. No differences were observed between monolateral and bilateral cryptorchidism patients. Conclusions Early prolonged hormonal therapy is advisable in all patients with cryptorchidism independently from the surgical option of promoting testicular descent to the scrotum. Hormonal therapy provides in our study better chance to obtain adequate sperm quality in adult life.